Differentiated learning design of independent curriculum based on project-based learning supports creative thinking skills in Indonesian language learning - Ayudia, Alda Marsya; Haryadi, Haryadi; Setyaningsih, Nas Haryati (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
Differentiated learning is one of the characteristics of the independent curriculum. It is important for educators to conduct, test, and create such learning to support the success of the learning process. This research is a conceptual research that aims to provide an idea by collaborating differentiated learning with a project-based learning model to support creative thinking skills in Indonesian language learning. The method used in this research islibrary research with a qualitative approach. Data collected from various literatures in the form of books, journals, research notes, permendikbud, are used to design learning designs. The results of this research are in the form of recommendations for differentiated learning design ideas based on project-based learning to support creative thinking skills on Indonesian anecdote text material for class X SMA. The design is structured with a series of learning activities guided by the four aspects of differentiated learning. This learning design is expected to help improve creative thinking skills and support the implementation of independent curriculum learning.